Lack of myeloid cell infiltration as an acquired resistance strategy to immunotherapy. Issue 2 (1st September 2020) - Beyranvand Nejad, Elham; Labrie, Camilla; Abdulrahman, Ziena; van Elsas, Marit J; Rademaker, Eva; Kleinovink, Jan Willem; van der Sluis, Tetje C; van Duikeren, Suzanne; Teunisse, Amina F A.S; Jochemsen, Aart G; Oosting, Jan; de Miranda, Noel F C C; et al.
Abstract : Background: Immunotherapy of cancer is successful but tumor regression often is incomplete and followed by escape. Understanding the mechanisms underlying this acquired resistance will aid the development of more effective treatments. Methods: We exploited a mouse model where tumor-specific therapeutic vaccination results in tumor regression, followed by local recurrence and resistance. In depth studies on systemic, local and tumor intrinsic changes were performed with flow and mass cytometry, immunohistochemistry, transcriptomics and several perturbation studies with inhibitors or agonistic antibodies in mice. Main findings were recapitulated in vaccinated patients. Results: Full tumor regression and cure of tumor-bearing mice is dependent on the magnitude of the vaccine-induced T-cell response. Recurrence of tumors did not involve classical immune escape mechanisms, such as antigen-presentation alterations, immune checkpoint expression, resistance to killing or local immune suppression. However, the recurrent tumors displayed a changed transcriptome with alterations in p53, tumor necrosis factor-α and transforming growth factor-β signaling pathways and they became immunologically cold. Remarkably, ex vivo cell-sorted recurrent tumors, directly reinjected in naïve hosts retained their resistance to vaccination despite a strong infiltration with tumor-specific CD8 + T cells, similar to that of vaccine-responsive tumors. The influx of inflammatory mature myeloid effector cells in the resistant tumors, however, was impaired and this turned out to be the underlying mechanisms as restoration of inflammatory myeloid cell infiltration reinstated the sensitivity of these refractory tumors to vaccination. Notably, impaired myeloid cell infiltration after vaccination was also associated with vaccine resistance in patients. Conclusion: An immunotherapy-induced disability of tumor cells to attract innate myeloid effector cells formed a major mechanism underlying immune escape and acquired resistance. These data not only stresses the importance of myeloid effector cells during immunotherapy but also demands for new studies to harness their tumoricidal activities.